Analisa Kualitas Layanan pada Industri Jasa Boga - Rina Inderayani; Wahyu Supartono; Didik Purwadi (agriTECH, 2003)
The growth of income, knowledge, jobs, and work places supported the existence of the food service industry to fulfill the society's need To increase the consumer's satisfaction, it was needed to measure the service quality. The service quality was measured based on several variables: tangibles, responsiveness, reliability, assurance, and empathy, which ordered by SERVQUAL instruments. The research was conducted by using questionnaire which was spread out to the consumers. The research methodology was purposive random sampling. The data were analyzed by product moment correlation test and Alpha technique for reliability test. The assumption for the double regression model had to fulfill following criteria's: no multicolinearity no autocorrelation, and heteroscedasticity which could be ignored. The results showed, that consumer's acceptance level for service quality was high, which could be ranked as follow: reliability (highest), assurance, tangibles, responsiveness, and empathy (lowest). Double regression model for the quality service was : Y = 1.377 + 3.99x10-2X17.278x104X2– 4.673x10-2X3 + 0.118X, + 2.381x10'2X3, which meant variable assurance (X4) gave the highest contribution to the consumer's satisfaction